Fat and breast cancer. - Kinlen, L (1987)
Breast cancer mortality and incidence in different countries show a strongly positive correlation with the per caput consumption of fat. In addition, the disease has increased among the Japanese, both in Japan and in the United States, and in both groups fat consumption has been increasing. In contrast, both case-control and prospective studies have on the whole failed to confirm the relationship. Despite these negative findings, the hypothesis that fat causes breast cancer has continued to be popular. The evidence for fat as a cause of breast cancer seems to have been exaggerated, and insufficient attention given to alternative explanations for the geographical correlations and for the changes among the Japanese in the frequency of the disease. These include the effects on breast cancer risk of body weight, body size, age at menarche (all influenced by excess calories) and age at the birth of the first child, as well as effects of obesity on the fatality rate in breast cancer. Evidence is lacking that the source of calories is important.